2008
DOI: 10.1007/s11010-008-9981-4
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone, but not estradiol, synchronizes circadian oscillator in the uterus endometrial stromal cells

Abstract: The circadian oscillator is generated within the suprachiasmatic nuclei and synchronizes circadian clocks in numerous peripheral tissues. The molecular basis is composed of a number of genes and proteins that form transcriptional and translational feedback loops. Such molecular oscillators are also operative in peripheral tissues, including in the uterus. Although ovarian steroids regulate the function of uterine endometrial stromal cells, the modulation of ovarian steroids on the circadian rhythms remains unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 46 publications
0
24
0
1
Order By: Relevance
“…In some experiments, bioluminescence recording was performed in the presence of 5% (vol/vol) charcoal-treated FBS in which steroid hormones were free. Luciferase activity was chronologically monitored at 37°C in 5% CO 2-95% air with a Kronos Dio AB-2550 luminometer (ATTO, Tokyo, Japan) interfaced to a computer for continuous data acquisition, as described (20,24). Bioluminescence records were detrended from the raw data (57).…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some experiments, bioluminescence recording was performed in the presence of 5% (vol/vol) charcoal-treated FBS in which steroid hormones were free. Luciferase activity was chronologically monitored at 37°C in 5% CO 2-95% air with a Kronos Dio AB-2550 luminometer (ATTO, Tokyo, Japan) interfaced to a computer for continuous data acquisition, as described (20,24). Bioluminescence records were detrended from the raw data (57).…”
Section: Animalsmentioning
confidence: 99%
“…Dissecting the roles of clock genes in peripheral tissues may lead to new insights into this critical but poorly understood process. Circadian clock genes are rhythmically expressed in various peripheral tissues, including liver, muscle, kidney, heart, ovary, and uterus (9,15,21,24,38). The molecular oscillations underlying the generation of circadian rhythmicity in mammals develop gradually during ontogenesis (46).…”
Section: E649 Contribution Of Fsh and T3 To Circadian Clocksmentioning
confidence: 99%
“…Several recent studies have demonstrated that circadian clock genes are rhythmically expressed in the uterus (3,10,19,23,36,40). Rev-erb␣, which is a circadian transcriptional repressor, has a key role in several metabolisms such as adipocyte differentiation, glucose metabolism, and thermogenesis (6,8,13).…”
mentioning
confidence: 99%
“…The stroma cells were treated with dexamethasone or forskolin. In the stroma cells prepared from intact immature rats, cyclic Per2 oscillation was observed after exposure to dexamethasone or forskolin (Fig 3, a & e) (Hirata et al, 2009). This suggests that the glucocorticoid response element (GRE) and cAMP response element (CRE) sites in the rat Per2 promoter are operative and transactivate the transcription of the Per2 gene (Travnickova-Bendova et al, 2002;Yamamoto et al, 2004).…”
Section: Circadian Rhythm In Uterine Cells Under Hormonal Stimulationmentioning
confidence: 88%
“…The circadian clock system may contribute to the progress of follicular development, luteinization and luteolysis, and steroid hormone-induced proliferation and differentiation of uterine cells through fluctuating hormones. Recently, there is a growing body of evidence that circadian clock genes are expressed in reproductive tissues including the ovary and uterus (Johnson et al, 2005;Nakamura et al, 2005;Fahrenkrug et al, 2006;Dolatshad et al, 2006;Karman & Tischkau, 2006;He et al, 2007aHe et al, , 2007bHe et al, , 2007cNakao et al, 2007;Hirata et al, 2009;Sellix & Menaker, 2010;Uchikawa et al, 2011). Many regulatory elements are located at the upstream of clock genes, such as steroid hormone response element half-sites and the adenosine 3',5'-cyclic monophosphate (cAMP) response element site as well as E-box and D-box elements.…”
Section: Introductionmentioning
confidence: 99%